Contemporary Discourse on Citizenship: An Islamic Perspective - Islam, Nasser Ul; Dar, Showkat Hussian (Islamic Research, 2023)
The pre-modern political frameworks of Muslim institutions, rooted in classifications like Dār al-Islam (Abode of Islam) and Dār al-Harb (Abode of War), are no longer fully compatible with the modern nation-state system. Contemporary terms such as Dār alShahādah (Abode of Testimony), Dār al-Ahd (Abode of Truce), and Dār al-Amān (Abode of Peace) have emerged as additions to the classical framework to address evolving sociopolitical contexts. This study aims to analyze the contributions of modern Muslim scholars and reformist thinkers to the development and reinterpretation of these classifications and their relevance to contemporary citizenship (Muwātana). Through a historical and analytical approach, the paper traces the evolution of the concept of citizenship within Islamic political thought, examining its transition from the Caliphate era (632–661 C.E) to the Ottoman Empire (1299–1924 C.E) and beyond. Special emphasis is placed on the reinterpretation of these concepts in light of Darūrah (necessity). The study reveals that the modern reinterpretations of classical frameworks offer a more inclusive and cohesive understanding of citizenship, treating all individuals equally within the nation-state paradigm. These developments reflect the adaptability of Islamic legal and political thought in addressing contemporary challenges. By exploring the evolution of citizenship within Islamic political history, this research underscores the necessity of reimagining classical frameworks to align with current socio-political realities, fostering greater inclusivity and harmony within diverse nation-state systems.